Acute Appendicitis with Unexpected Atypical Findings – A Case Report - Malik, Afrah; Niaz, Asif; Ahmad, Ejaz; Younas, Muhammad Tahir (Pakistan Armed Forces Medical Journal, 2024)
An aberrant position of the appendix may present with atypical abdominal pain; however, in our case, right hypochondrial pain was associated with surprising incidental findings. We present a unique case that, to the best of our knowledge, has not been reported in previous literature. A 35-year-old female came to the Emergency Department with a four-day history of RUQ pain. Examination revealed tender right hypochondrial with the palpable liver. Ultrasound showed a solid cystic hyperechoic lesion 9.9 x 8.9 x 13.8 cm in the liver. To further investigate, a contrast-enhanced computed tomography abdomen showed a non-enhancing, well-demarcated ovoid mixed density area in the right posterior upper abdomen with the internal layering of its contents having characteristics concerning a retroperitoneal teratoma and a retrocausal appendix with significant surrounding inflammatory changes (Figure). The patient then underwent a laparotomy, appendectomy, and teratoma removal. She recovered well without any complications. Hence, clinicians should be aware of rare causes of abdominal pain that require advanced investigations to prevent delays in diagnosis.